Rod length influence in torque measurement of SPT-T test - Peixoto, Anna S. P. [UNESP]; Antenor, Valéria B. [UNESP]; Ramos, Thiago M. [UNESP]; David, Rita [UNESP] (American Society of Civil Engineers (ASCE), 2007)
Since Ranzini suggested supplementing the SPT test with measurement of the torque required to turn the split spoon sampler after driving, many Brazilian engineers have been using this in the design of pile foundations. This paper presents a study of the rod length influence in the torque measurement. A theoretical study of material resistance considering torsion and bending in a thin wall tubular steel shaft was performed. It makes possible to conclude that the shearing tension caused by the proper weight represents less than 1% of the shearing tension caused by the turning moment. In addition, an experimental study was done with electric torquemeters fixed in a horizontal rod system. The tests were being carried out to analyze rods of one meter to twenty meters in length and the measurements were collected at the ends of each rod length verifying the efficiency data. As a result, it is possible to verify that the torque difference through rod length is lower than minimum scales of mechanical torquemeters that are used on practical engineering. Also a fact to be considered is a big torque loss for values under 20 N.m of applied torque. This way, the SPT-T is not adequate to low consistency soil. Copyright ASCE 2007.
Keywords: Rod influence; SPT-T; Torque measurement; Bending (deformation); Measurement theory; Shearing; Torque meters; Torsional stress; Material resistance; Rod length; Turning moment